Busulfan is effective second-line therapy for older patients with Philadelphia-negative myeloproliferative neoplasms intolerant of or unresponsive to hydroxyurea. Issue 1 (2nd January 2017) - Douglas, Genevieve; Harrison, Claire; Forsyth, Cecily; Bennett, Michael; Stevenson, William; Hounsell, John; Ratnasingam, Sumita; Ritchie, David; Ross, David M.; Grigg, Andrew
Abstract: Hydroxyurea (Hu) is widely used as first-line cytoreductive therapy for patients with high-risk Philadelphia-negative myeloproliferative neoplasms (Ph-neg MPN), but a small proportion of patients have refractory disease or experience adverse effects. Studies have demonstrated busulfan (Bu) to be an active first-line agent, but data on its role as second-line or later therapy are minimal. To evaluate its efficacy and safety in this context, we undertook a multicenter audit of Ph-neg MPN patients who had received Bu as therapy for Hu intolerance or failure. Of 51 patients identified, 38 (75%) achieved either complete or partial hematological response following at least one Bu cycle. Bu was generally well tolerated, with only 21/135 (15%) cycles complicated by adverse effects, predominantly cytopenia; only 6% of cycles were ceased due to treatment complications. Bu is an effective and well-tolerated agent in patients with Ph-neg MPN in the setting of Hu intolerance or unresponsiveness.